Learning Innovations: Students’ Interest and Motivation on STEAM-PjBL - Suryaningsih, Siti; Nisa, Fakhira Ainun; Muslim, Buchori; Aldiansyah, Fauzan (International Journal of STEM Education for Sustainability, 2022)
The purpose of this study was to 1) determine the results of the prerequisite test of the research instrument consisting of tests of validity, reliability, and normality, 2) know students' responses to interest and motivation to learn using chemistry learning innovations. The method used is descriptive quantitative. A sample of 76 students was selected by purposive sampling at one of the senior high schools in Indonesia. Data was collected using a questionnaire instrument with ten items arranged based on a Likert scale based on student interest and motivation indicators on the acid-base titration concept. The instrument used was declared valid, and reliability was proven by a corrected item-total correlation of 10 items. Each of them has a value of more than 0.325. A reliability value of 0.785 and a significance value of 0.2 indicates that the data is normally distributed. The Science, Technology, Engineering, Arts, and Mathematics-Project Based Learning (STEAM-PjBL) innovation received a good response from students in the form of a high percentage of interest and learning motivation. Students' interest in learning got an average score of 4.17 in the high category of 83.4%. Likewise, learning motivation scored 4.22 in the high category of 84.4%. In general, student responses gave positive responses or agreed to the application of STEAM-PjBL in chemistry learning because it gave students high interest and motivation to learn. The results of this study can be used as innovations in the science learning process.